Delivering good aid in hard places: The Yemen Social Fund for Development approach - Lamis Al-Iryani; Alain De Janvry; Elisabeth Sadoulet (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The Yemen Social Fund for Development (SFD) was established in 1997 with the support of the international community, and in particular the World Bank, to combat national poverty and reinforce the limited existing social safety net. Since its inception, SFD has been widely viewed as successful in implementing programmes in rural and urban communities throughout the country and has steadily expanded and scaled-up its activities, despite Yemen's weak state and political unrest. It provides in that sense a model of how to deliver good aid in hard places, with relevance for other countries with similar conditions. Drawing on first hand experience with the SFD and on a review of results from rigorous impact evaluations, this paper argues that SFD's success has been due primarily to four factors: (1) stakeholder ownership over projects due to its close work relationship with local communities following a demand-driven approach; (2) trust based on its political neutrality in allocating resources; (3) flexibility due to its mode of project funding and operations; and (4) relevance of SFD interventions for beneficiaries who in reciprocity provide strong support to its programmes. The paper discusses how these factors can be transposed to other hard places using the social fund approach to deliver good aid.
Keywords: F35; O19; O22; H10; 330; international aid; fragile states; aid effectiveness; social funds